2008
DOI: 10.1186/1744-8069-4-3
|View full text |Cite
|
Sign up to set email alerts
|

Perineural Resiniferatoxin Selectively Inhibits Inflammatory Hyperalgesia

Abstract: Resiniferatoxin (RTX) is an ultrapotent capsaicin analog that binds to the transient receptor potential channel, vanilloid subfamily member 1 (TRPV1). There is a large body of evidence supporting a role for TRPV1 in noxious-mediated and inflammatory hyperalgesic responses. In this study, we evaluated low, graded, doses of perineural RTX as a method for regional pain control. We hypothesized that this approach can provide long-term, but reversible, blockade of a portion of nociceptive afferent fibers within per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
43
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 33 publications
6
43
0
Order By: Relevance
“…At the same time, the rats did not exhibit autotomy behaviors that commonly accompany sciatic nerve transection [56][57][58]. These results are consistent with earlier studies on peripheral injections of RTX into the hind paw [32], perineurally [38,55], or directly into rat or monkey trigeminal [33,59]. These data suggest that our TRPV1 PAM is producing the expected on-target effects and does not produce unexpected sensory abnormalities.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…At the same time, the rats did not exhibit autotomy behaviors that commonly accompany sciatic nerve transection [56][57][58]. These results are consistent with earlier studies on peripheral injections of RTX into the hind paw [32], perineurally [38,55], or directly into rat or monkey trigeminal [33,59]. These data suggest that our TRPV1 PAM is producing the expected on-target effects and does not produce unexpected sensory abnormalities.…”
Section: Discussionsupporting
confidence: 81%
“…This localized analgesia in the midplantar and distal regions suggests that the nerve terminal inactivation is confined to the nerve endings in the immediate vicinity of the injection site and to axons projecting through it; an effect we have demonstrated previously with peripherally administered resiniferatoxin [8]. We refer to the process involving nerve endings as "nerve terminal inactivation" or "deactivation," rather than complete ablation, since the nerve endings can grow back and become active again [32,55]. We also distinguish inactivation/deactivation from desensitization, the latter referring to the progressive decrement in response upon multiple, successive applications of a vanilloid agonist; desensitization is an endpoint frequently investigated in electrophysiological experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Several groups have found small increase in thermal nociceptive threshold 28,41 but others reported little if any effect in hot plate tests 42,43 . It was reported that perineural resiniferatoxin selectively inhibits inflammatory hyperalgesia 44 . We have determined in serial experiments that the heat threshold increase depends on the efficacy of the RTX treatment; heat insensitivity of the animal becomes more pronounced if RTX ablates TRPV1 + nociceptors almost completely.…”
Section: Discussionmentioning
confidence: 99%
“…Intrathecal application (18,19) can encompass multiple dermatomes, whereas an intraganglionic (14) or periganglionic (20) injection can restrict the lesion to single unilateral segments. Peripheral application under the skin (21,22), adjacent to the nerve (23,24), or intra-articularly (25,26) confines the inactivation to the local nerve terminals, achieving long-term but reversible regional analgesia. These procedure-based applications can be targeted to a patient's pain problem on an individualized basis, and allow for focused pain alleviation with minimal impact on surrounding sensory nerve fibers (18).…”
Section: Resultsmentioning
confidence: 99%